Si-based magnetic tunnel transistor with high transfer ratio - Jang, SH; Kang, T; Lee, JH; Kim, KY (ELSEVIER SCIENCE BV, 2004)
The properties of Si-based magnetic tunnel transistor (MTT) with high transfer ratio are presented. MTTs were prepared on Si(100) substrates by magnetron sputter deposition. Magnetocurrent ratios of 53-55% and high transfer ratios of (1-2) x 10(-4) for emitter-base bias 1.5-2 V were obtained at 77 K. High collector current value of about 0.9 muA for 2 V was also obtained. (C) 2003 Published by Elsevier B.V.